DESCRIPTION OF ODONTOGENIC INFECTIONS RELATED TO ORAL HYGIENE AT SDN 3 KALIBAWANG WONOSOBO INDONESIA - Ferlita Shafri Djohan, Frita (Fakultas Kedokteran Gigi Unjani, 2024)
Odontogenic infection is a disease of the oral cavity, the leading cause of caries and periodontal disease. Inadequate ability to brush teeth is one of the causes of this pathological condition. This study aims to determine the description of odontogenic infections at SDN 3 Kalibawang, Kalibawang District, Wonosobo Indonesia. The research procedure used a total sampling technique, and the research variable was students at SDN 3 Kalibawang Wonosobo who experienced odontogenic infections. The tools used in this research were an Android smartphone, the HI BOGI application, and Microsoft Excel. Results odontogenic infections at the school were 70.21% positive in 33 students. The severity of untreated caries by gender: boys are bigger at 61.7%, while girls are 36.3%. Kalibawang State Elementary School 3, Wonosobo Regency, tested positive for an odontogenic infection, one of the causes of which could be triggered by inadequate tooth brushing. DOI : 10.54052/jhds.v4n1.p91-104